Anti-Neutrophil Cytoplasmic Antibody-Associated Glomerulonephritis and Malignancy: A Case of a Patient Diagnosed with Renal Failure and Pulmonary Carcinoma Concurrently. Issue 14 (March 2021) - Asakura, Maki; Akimoto, Tetsu; Ohara, Ken; Masuda, Takahiro; Ono, Yuko; Saito, Osamu; Nagata, Daisuke
A 70-year-old man presented with proteinuria, microscopic hematuria, and an increased level of serum creatinine. A systemic workup revealed that the patient had bronchogenic carcinoma and anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis concurrently. Despite the increase in the cumulative number of publications on paraneoplastic glomerulopathies, an awareness of the link between cancer and ANCA-associated glomerulonephritis is lacking. We strongly recommend the accumulation of more cases similar to our own, thereby allowing us to clarify the management strategies as well as the nature of this disease condition more precisely.